Nuansa Dwika Aulia1, Kuswanto2, EVALUASI PENGELOLAAN SAMPAH DI TEMPAT PENGOLAHAN SAMPAH TERPADU KELOMPOK SWADAYA MASYARAKAT “SAE” KELURAHAN PURWOKERTO WETAN - Agnes Fitria Widiyanto; Nuansa Aulia Dwika; Suratman Suratman; Saudin Yuniarno; Kuswanto Kuswanto (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Purwokerto Wetan Village is the largest contributor to the Waste Bank in Banyumas Regency, with a total of 51585.48 kg of waste from a total of 19 KSM registered in the SalinMas Application or Banyumas Online Garbage. The objectives of this research are 1) to evaluate the institutional, regulatory, financing, technical operational aspects and community participation in waste management at TPST KSM Sae, Purwokerto Wetan Village. The design of this research is descriptive qualitative with the subject of the research, namely 1) Key informants: KSM Sae Manager and Purwokerto Wetan Village Officers in the Waste Sector. 2) Main informants: Sanitarian at the Purwokerto Timur I Health Center and the Waste Sector at the Banyumas Regency Environmental Service. 3) Supporting informants: Residents of Purwokerto Wetan Village, users of SalinMas and local community leaders. Data collection was carried out by in-depth interviews and observations. The validity of the data was tested by triangulation of sources and methods. The results and discussion of this research are 1) Institutional aspect, KSM Sae has met the requirements written in SNI 3242-2008. There are no human resources that work in the field of waste management. 2) Regulatory aspects, most of the respondents do not know the legal basis used for the formation of KSM at the international, national and regional levels. 3) The financing system at KSM Sae is in accordance with SNI 32420-2008 that for the procurement of equipment is assisted by DLH while the operational and maintenance costs are managed by KSM itself through cash. And the amount of dues or levies that must be paid by residents is not listed in the Banyumas Regency Regional Regulation Number 9 of 2020, but the amount is returned to the authority of KSM. 4) The operational techniques applied at KSM Sae are in accordance with SNI 3242-2008 and Banyumas Regency Perda Number 9 of 2020. There is no process for processing waste into energy recycling and processing household B3 waste. 5) Community participation in Purwokerto Wetan Village is still lacking. This can be seen from the not yet optimal, this is due to the lack of public awareness to manage waste from the source.